2000
DOI: 10.1530/revreprod/5.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress on reproduction in non-rodent mammals: the role of glucocorticoids and sex differences

Abstract: The means by which stress influences reproduction is not clearly understood, but may involve a number of endocrine, paracrine and neural systems. Stress impacts on the reproductive axis at the hypothalamus (to affect GnRH secretion) and the pituitary gland (to affect gonadotrophin secretion), with direct effects on the gonads being of less importance. Different stressors have different effects and there are differences in response to short-and long-term stress. Many short-term stresses fail to affect reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 10 publications
5
89
1
2
Order By: Relevance
“…Catecholamines, such as epinephrine and norepinephrine, are also released as part of the fight-or-flight response to stress. Together, the suite of hormones activated by this response influence many processes in the body including heart rate, metabolic rate, energy allocation, growth, reproduction, immune response, memory, and behavior, allowing an animal to react appropriately to the stress, which ultimately promotes survival (Breuner et al, 2013;Brilion et al, 1995;Connell and Davies, 2005;Khani and Tayek, 2001;Maule et al, 1987;Romero and Butler, 2007;Tilbrook et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Catecholamines, such as epinephrine and norepinephrine, are also released as part of the fight-or-flight response to stress. Together, the suite of hormones activated by this response influence many processes in the body including heart rate, metabolic rate, energy allocation, growth, reproduction, immune response, memory, and behavior, allowing an animal to react appropriately to the stress, which ultimately promotes survival (Breuner et al, 2013;Brilion et al, 1995;Connell and Davies, 2005;Khani and Tayek, 2001;Maule et al, 1987;Romero and Butler, 2007;Tilbrook et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although the evidence supporting the linkage between metabolic impairments and reproductive disturbances is strong, others have proposed the idea of a stress-related mechanism in which reproductive function is compromised secondary to the activation of the stressresponse systems: the hypothalamic-pituitary-adrenal (HPA) and sympathoadrenal axes (Tilbrook et al 2000(Tilbrook et al , 2002. Although this review has focused on metabolic stress, it has also been shown that immune stress (i.e.…”
Section: Stress Responses As Metabolic Modulators Of Hpg Axis Functionmentioning
confidence: 97%
“…At the same time, however, corticosterone may downregulate processes such as reproduction and growth that are not required for immediate survival. Chronic elevation of plasma corticosterone concentration due to shortage of prey items, high predator density, high parasite load, or poor body condition can, for example, suppress reproduction (Tilbrook et al 2000;Wingfield and Sapolsky 2003;Petes et al 2007) because high plasma corticosterone concentration increases energy expenditure for self-maintenance (McEwen and Wingfield 2003;Cote et al 2006;Lynn et al 2010). Thus, elevated plasma corticosterone concentrations in reproducing females are typically viewed as having a negative impact on reproductive investment in terms of the energy budget.…”
Section: Do Gravid Females Become Selfish? Female Allocation Of Energmentioning
confidence: 99%